2019
DOI: 10.1002/sim.8359
|View full text |Cite
|
Sign up to set email alerts
|

Measurement error in continuous endpoints in randomised trials: Problems and solutions

Abstract: In randomised trials, continuous endpoints are often measured with some degree of error. This study explores the impact of ignoring measurement error and proposes methods to improve statistical inference in the presence of measurement error. Three main types of measurement error in continuous endpoints are considered: classical, systematic, and differential. For each measurement error type, a corrected effect estimator is proposed. The corrected estimators and several methods for confidence interval estimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 44 publications
(128 reference statements)
0
25
0
Order By: Relevance
“…The technical performance characteristics of a QIB, that is, its precision and bias, are essential in understanding individual patient’s QIB measurements and planning and interpreting clinical trial results. Nab et al 2 and Obuchowski et al 4 have shown that imprecision in QIBs increases the type II errors in clinical trials. Furthermore, in this article, we have illustrated that estimates of treatment effects are biased when the slope of the regression of measured versus true biomarker values differs from one.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The technical performance characteristics of a QIB, that is, its precision and bias, are essential in understanding individual patient’s QIB measurements and planning and interpreting clinical trial results. Nab et al 2 and Obuchowski et al 4 have shown that imprecision in QIBs increases the type II errors in clinical trials. Furthermore, in this article, we have illustrated that estimates of treatment effects are biased when the slope of the regression of measured versus true biomarker values differs from one.…”
Section: Resultsmentioning
confidence: 99%
“…Good technical performance validation studies are essential when developing and testing a QIB for its potential use in a clinical trial. 2,4 Test–retest studies, in which subjects are imaged two or more times over a short period, provide estimates of a QIB’s precision. 5 Phantom studies, where synthetic objects with known properties are imaged, provide estimates of a QIB’s bias.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations